(3fXe GdJNWjW h GdQbGHI Ydi GdGfJGL h GdYedjGJ (B/s - (3eMLhH, HSeGf ajUds; (3GdGJQhTj, YbjdI eUWai s; (3OGhO, ZSGf bGSe s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2005)
(3fXGe JNWjW GdGMJjGLGJ ef GdehGO (B(MRP) (3GVGaI Gdi fXGe GdGfJGL GdBfj (B(GIT) (3h cPG adSaI JcfhdhLjG GdGfJGL GdGeKd h aj GdGNjQ GdYdGbGJ GdJcGedjI h GdGJLGgGJ GdMOjKI aj fXe GdGfJGL h GdYedjGJ(B.s
Keywords: (3GdGfJGLs; (3GdJNWjWs; (3GdQbGHIs; (3GdYedjGJ s